GAMBARAN STATUS GIZI ANAK KELAS VI DI SEKOLAH DASAR MIFTAKHUL ULUM SURABAYA - Herdiani, Novera; Afridah, Wiwik (Jurnal Ilmu Kesehatan dan Kesehatan, 2018)
Abstract: Background, nutritional status is a description of balance between the need of nutrientsfor keeping a good life, to maintenance normal body function also energy production in one sideand the consumption of nutrients in the other. Children in elementary school are the best target forimprovement of community nutrition because in the childhood the function of the brain organbegan to form so the development of intelligence is quite rapid. Lack of nutritional intake inchildren can inhibit the physical growth and thinking ability in children and subsequently reduce inlearning interest. Therefore the nutritional status of the children must detect immediately to carryout the preventive measurements. Objective, the purpose of this study is to know the nutritionalstatus of children at grade VI in elementary school Miftakhul Ulum Surabaya based on height andweight. Methods, this study is a quantitative descriptive using survey method, weighting indexinstrument by height in children aged 6?17 years old from Health Department in 2011. This studyused the measurement of body weight and height. Subjects of this study were all students at grade VIin elementary school Miftakhul Ulum Surabaya, which amount 81 children. Data collecting techniques use anthropometric measurements which include measurement of body weight and heightthen calculated base of data analysis techniques using quantitative descriptive with percentage.Result, study results showed most of the students were 12 years old (56.80%), mostly male (55.60%).most of them have body height 130?140 cm (37.00%), and body weight 31?40 kg (46,90%). Malechildren have more problems with their nutritional status (51.10%). Male children much oftenhave underweight and over weight (13.30%) than girls. By the increasing their age, their BMI willbe normal category (100%). By the age of 13 and 14 years old, the children will not have underweight (0%). Conclusion, based on the nutritional status of all children at grade VI, it can beconcluded that the nutritional status of children at grade VI in elementary school Miftakhul UlumSurabaya is in underweight category (very thin and lean) with percentage 56.80%. While the normal weight percentage 32.10%, and over weight (fat and obesity) with percentage 11.10%.